Nurturing work engagement: unravelling the impact of servant leadership, employee emotional intelligence, and work-family conflict - Lim, Prisco; Zawawi, Dahlia; Abdul Aziz, Yuhanis (Universiti Putra Malaysia, 2024)
This study explores the influence of servant leadership (SL), emotional intelligence (EI), and work interfere with family (WIF) on work engagement (WE) among the service sector workforce in Klang Valley, Malaysia. A quantitative approach via survey was administered to 150 employees from the food and beverage, retail and wholesale trade, and accommodation sectors. The Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis revealed that SL and EI positively affect WE, while WIF negatively impacts WE among service sector employees. The practical implications emphasise the importance of fostering EI, implementing SL practices, and addressing WIF to enhance employee WE. This study also offers theoretical contributions to further enhance the understanding of these factors within the Job Demands-Resources (JD-R) framework.